Seasonal performance of finishing steers - Mintert, J.; Langemeier, Michael R.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Analysis of 10 years of closeouts from a western Kansas feedlot demonstrated that steer performance exhibits significant seasonal variation. Steers weighing 700 to 800 lb when placed on feed in September through December had feed conversions roughly 12% higher than those placed in March and April. Although feed conversion varied seasonally, dry matter feed intake varied much less, causing daily gain to mirror feed conversion. Gain was seasonally highest for steers placed in March and April and lowest for those placed in September through December. Cattle feeders should consider these variations in seasonal performance, as they develop profit projections for steers being placed on feed.
Keywords: Beef; Feeding performance; Seasonality; Steers